Pengaruh Kualitas Produk, Citra Merek dan Harga Terhadap Keputusan Pembelian Terang Bulan Mas Iping di Sidoarjo - Jaya, Arief Danan Jaya; Jaya, Arief Danan (Innovative Technologica: Methodical Research Journal, 2024)
This study aims to determine the effect of product quality, brand image, and price on purchasing decisions at Mas Iping's moonlight in Sidoarjo. This research uses quantitative research with hypothesis testing. The sample used in this study were 100 customers of the bright moon Mas Iping in Sidoarjo. The data analysis technique used in this research is multiple linear regression analysis, coefficient of determination (R2), t test, F test, and classical assumption test using SPSS statistical software version 22.0. The main data in this study came from a questionnaire. The results of this study prove that product quality has an effect on purchasing decisions for Mas Iping's moonlight in Sidoarjo. Brand image influences the purchase decision of Mas Iping's moonlight in Sidoarjo. Price influences the purchase decision of Mas Iping's moonlight in Sidoarjo. Thus, it can be concluded that product quality, brand image, and price simultaneously influence the purchase decision of Mas Iping's moonlight in Sidoarjo.